2015
DOI: 10.3997/2214-4609.201413251
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Gas Pockets Detection by High-resolution Volumetric Q-tomography Using Accurate Frequency Peak Estimation

Abstract: Conventional imaging does not deal adequately with absorption, especially in the case of strong anomalies. Over recent years, many authors have proposed to compensate the absorption loss effects inside of the migration through the use of an attenuation model. Q tomography has been developed for estimating this attenuation model but is generally limited to estimating attenuation in predefined anomalies. In this paper, we explain how we developed a high-resolution volumetric Q tomography to attain an accurate vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…ere is no presence of absorption (Q) anomalies in the data, so a constant background Q quality factor of 150 using the spectral ratio method was derived and used for QPSDM. It is worth mentioning that another technology for absorption inversion called "volumetric Q tomography" (Gamar-Sadat et al, 2015) was tested on a small swath. e test result showed that there is no signi cant spatial variation in the Q model for this data, and both models were able to produce similar QPSDM images.…”
Section: Q-compensated Prestack Depth Migrationmentioning
confidence: 99%
“…ere is no presence of absorption (Q) anomalies in the data, so a constant background Q quality factor of 150 using the spectral ratio method was derived and used for QPSDM. It is worth mentioning that another technology for absorption inversion called "volumetric Q tomography" (Gamar-Sadat et al, 2015) was tested on a small swath. e test result showed that there is no signi cant spatial variation in the Q model for this data, and both models were able to produce similar QPSDM images.…”
Section: Q-compensated Prestack Depth Migrationmentioning
confidence: 99%
“…Estimation of the Q model for this survey was done using the frequency peak shift (FPS) method and volumetric Q tomography (Gamar-Sadat et al, 2015). e proposed ow is able to estimate a background Q model while localizing small anomalies, especially ones related to gas.…”
Section: Q Tomography and Q Psdmmentioning
confidence: 99%
“…Our approach consists of calculating a prestack dense effective Q-volume in four dimensions (time, inline, crossline, offset), using the shift of the frequency peak (Gamar et al, 2015). The picking of the frequency peak is done on amplitude spectra computed around the maximum of the autocorrelation of the data.…”
Section: Volumetric Q-tomographymentioning
confidence: 99%
“…For this challenging processing project, we applied a workflow that uses volumetric Q-tomography for converting volumetric, effective Q-measurements made on prestack data into a 3D interval Qmodel. To compute the effective Q-volume in the prestack domain, we use a method based on the frequency peak shift (Gamar et al, 2015). The absorption effects can be accurately compensated within the imaging process (Xie et al, 2009) thanks to an interval Q-model computed by tomography (Xin et al, 2008, Cavalca et al, 2011, Gamar et al, 2015.…”
Section: Introductionmentioning
confidence: 99%